Substitution of pork fat with hydroxypropylated tapioca (Manihot ultissima Pohl.) starch in low-cost chicken-based longganisa - Dilao, Tiffany Fantonalgo
ABSTRACT This study was conducted to substitute pork fat with hydroxypropylated tapioca starch in the formulation of low-cost chicken-based longanisa. The maximum level of substitution without significantly affecting (α=0.05) the acceptability and the sensory attributes of the product was determined. The recommended usage levels (3-5%) of hydroxypropylated tapioca starch were used in the first phase of the study. In Phase I, fifty panelists evaluated the samples with varying levels of hydroxypropylated tapioca starch. The sample with 3% hydroxypropylated tapioca starch had acceptability scores higher than the control sample that contains pork fat. In phase II, products from the formulation selected in Phase I were prepared in three batches. The samples were then evaluated for difference due to production runs. The sensory evaluation results were subjected to ANOVA (α=0.05). No significant differences among samples were observed in any sensory attribute. This showed that the formulation was repeatable given that the procedure is strictly observed. The chemical analysis in Phase III showed that crude fat can be significantly reduced by substituting pork fat with hydroxypropylated tapioca starch in the formulation of low-cost chicken-based longanisa. The experimental product contained crude fat that was almost four times lower than that of the control product. The microbiological properties of the control and experimental product were similar. The cost of the experimental product was 10.44% lower than that of the control product.